The Effect Of Exercises Using External Distractions On the Accuracy of (10m) Penalty Shot For Futsal Players - Lazim, Asaad; Qassim, Ismael (Journal of Physical Education, 2017)
The training of players in conditions similar to the conditions of the games with external influences and stimuli help the players overcome many difficulties especially in futsal because it is a game of changing circumstances with multiple stimuli .The importance of research lies in using game – like conditions by exposing the player to various stimuli which helps him in the future to develop concentration, that isolates unwanted stimuli and focus on the accuracy of scoring during the penalty shot .The problem of research is the lack of attention to external distraction factors in any training module, especially in the penalty shot .The aims of the research was preparing exercises that develop the accuracy of the players ’correction during penalty shots with external stimuli and distractions as well as to recognizing the effect of these exercises. The researcher used the experimental method. The subjects were (20) players from the college of languages. They were randomly divided into two equal experimental and controlling .The exercise were applied to the experimental group for eight weeks, three units per week as well as the same repetitions of the controlling group without exposing them to any external effect. The results were presented through pre and posttests of the two groups. The researchers concluded were reached and concluded that the exercise of the effects of similar conditions of play has a positive effect on the development of the scoring performance and the accuracy penalty.